Malaysian maveric Mahathir Mohamad in turbulent times - Wain, Barr (Critical studies of the Asia Pacific series, 2012)
This second edition in paper back offers in a single comprehensive volume the misdeeds and scandals that occurred during Mahathir Mohamad two decades as prime minister of Malaysia and afterwards. It includes Mahathir's response to the first edition and engages with the debate about Mahathir's legacy.